PERANAN MACAM BAHAN ORGANIK DAN JARAK TANAM PADA TANAMAN BAWANG MERAH (Allium cepa fa. ascalonicum, L.) DI LAHAN PASIR ERUPSI MERAPI - Agus Suprapto; Historiawati Historiawati; Budi Aris Saputra (Universitas Tidar, 2017)
This research studised the role of organic material and plant distance on onion (Allium cepa fa. ascalonicum, L.) in the land of sand Merapi eruption. Research has been conducted on August 2016 to November 2016 in the village Sawangan, District Sawangan, Magelang, Central Java Province. Altitude of 485 m above sea level, the soil type Regosol with a pH of 5.5. This study used factorial experiment (3 x 3) were arranged in a complete randomized block design (RCBD) with three block. The first factor was the organic material that was cocopeat, husk charcoal and peat. The second factor was a plant distance of 15 cm x 20 cm, 20 cm x 20 cm and 25 cm x 20 cm. The results of the studies organic material response on all parameters. Plant distance 25 cm x 20 high give the most result in the number of leaves, number of tubers per hill, tuber fresh weight per hill, tuber dry weight savings per clump and crop growth rate. The combination of organic material and plant distance of the same response on all parameters.